A Literature Review of Green Human Resource Management for Gaining a Competitive Advantage - Johan Oscar Ong; Masydzulhak Djamil; Enny Ariyanto; Sugiyono Sugiyono (MIX: JURNAL ILMIAH MANAJEMEN, 2022)
Green human resource management (GHRM) plays an important role in organizations’ sustainable development strategies. However, there is still a research gap on the integration of available GHRM-related knowledge to gain a competitive advantage. Objectives: Thus, the purpose of this paper is to conduct a literature review on GHRM aimed at proposing detailed research on those gaps in order to gain competitive advantages for future studies. Methodology: First, this work applies the keyword GHRM and "competitive advantage" for articles above the year 2017 and selects articles indexed in Scopus only. We have conducted a preselect process to figure out the appropriate articles related to GHRM and competitive advantage. We have also selected and reviewed 18 articles discussing the relationship between GHRM and competitive advantage.Finding: Last, the study addresses research gaps and proposes a research framework for further studies.Conclusion: Analysis of the relevant literature is presented in descriptive analysis and a research framework that focuses on GHRM for a future research agenda. This review is important for researchers in GHRM to identify research gaps for competitive advantage. It is suggested that mediating variables, such as organizational citizenship behavior for the environment and environmental performance, have to be included in GHRM's future research to gain a competitive advantage.